2006
DOI: 10.1086/504469
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impact of Lyman Break Galaxies

Abstract: We perform cosmological simulations of galaxies forming at using the hydrodynamics grid code, Enzo. z p 3 By selecting the largest galaxies in the volume to correspond to Lyman break galaxies, we construct observational spectra of the H i flux distribution around these objects, as well as column densities of C iv and O vi throughout a refined region. We successfully reproduce the most recent observations of the mean H i flux in the close vicinity of Lyman break galaxies but see no evidence for the proximity ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Tasker & Bryan (2006) run a set of simulations similar to Li, Mac Low & Klessen (2005b) except that they include SN feedback and the gas is simulated on a grid. Even though their feedback implementation simply pours the feedback energy into the ISM, it proves effective at limiting star formation.…”
Section: Discussionmentioning
confidence: 99%
“…Tasker & Bryan (2006) run a set of simulations similar to Li, Mac Low & Klessen (2005b) except that they include SN feedback and the gas is simulated on a grid. Even though their feedback implementation simply pours the feedback energy into the ISM, it proves effective at limiting star formation.…”
Section: Discussionmentioning
confidence: 99%
“…At high redshifts, LBGs studies show that active star formation traced by the UV light resides preferentially in overdense regions Blaizot et al 2004;Giavalisco 2002;Steidel et al 1998;Tasker & Bryan 2006). At low redshift, Abbas & Sheth (2005) showed that the slope of the fitted power law is steeper in underdense regions, and that the correlation length is smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, limitations in computer power as well as in the efficiency of available algorithms, make it possible to resolve at best scales of 100 pc in cosmological simulations (very recent simulations have been able to achieve a resolution of less than 50 pc, but they can only cover the first few billion years of evolution 43 ). Simulations with resolution adequate to follow directly molecular clouds, interstellar turbulence and star formation do exist, but are restricted to studying an isolated galaxy 64,65 or a small region of a single galaxy 66 . Detailed numerical models of the effects of supernovae explosions also exist, but again they are restricted to a small volume of the ISM 67,68 .…”
Section: Modeling Issuesmentioning
confidence: 99%